ASSOCIATION OF UDDER BIOMETRY AND SKIN THICKNESS WITH MILK YIELD IN KANKREJ AND CROSSBRED COWS - Kshatriya, P S; Trivedi, M M; Dhami , A J (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Relationship between biometry of udder and skin thickness with milk yield was studied in 22 Kankrej and 26 crossbred (¼ HF x ¼ Jersey x ½ Kankrej) cows. Average evening milk yield on the test day was nonsignificantly higher in crossbred cows (3.52 kg) than the Kankrej cows (2.84 kg). Average udder length, width and depth in crossbred cows were 20.73, 23.31 and 8.00 inches, respectively. Corresponding values in Kankrej cows were 21.45, 23.09 and 7.77 inches. The skin thickness at all the three sites i.e. at neck, behind elbow and at flank was higher in Kankrej (7.86, 6.59 and 8.77 mm) than the crossbred cows (7.23, 5.46 and 7.00 mm, resp.). Correlation coefficients of milk yield with udder length, width and depth were positive and highly significant (P
Keywords: Cows; Udder biometry; Skin thickness; Relationships to milk yield